KELANGSUNGAN HIDUP KOMUNITAS ANAK MUDA PECINTA SENI (STUDI KASUS TENTANG KOMUNITAS GAYAM 16 DI YOGYAKARTA) - , SURYA P SHEINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gamelan is Indonesian traditional musical instrument which originally comes from Java and Bali. Gamelan is usually played in the traditional ceremony in Javanese culture and Balinese culture, so that it can not be separated from the daily live of Javanese and Balinese society itself. This research studies about how a group of youngsters struggles to maintain an organization, in the form of community, to defend the existence of gamelan musical instruments with their own way. Specifically, this research is focused on âKomunitas Gayam 16â which is one and only community that consistently keeps the existence of gamelan musical instrument in Yogyakarta until nowadays. The study was conducted over a period of approximately seven months ie from September 2013 to March 2014. Informants are some of the board members of Komunitas Gayam 16. Study began with the observation of daily activities, and also in-depth interviews. The writer found gamelan consists of a set of musical instruments in which includes various kinds of them. Some of them are kendang, saron, demung, bonang, kenong, gong, kempul, slenthem, siter and many more. This set of musical instruments ought to be played altogether at the same time to create a harmonically sounded music. Gamelan, especially in Yogyakarta, is a very well known musical instruments among the people. We often hear the term gamelan and at the same time can easily imagine the solid shape of it. However, the youth generation's enthusiasm for learning and understanding this kind of musical instrument is still too low. Some of the youngsters even consider that this kind of musical instrument is too old and it does not fit with the era of modernity now. Then, the existence of this traditional musical instrument is fading away in the youth generation. For that reason in this study, will be seen how the young people in Komunitas Gayam 16 uplifting traditional musical instruments, especially gamelan.